A COMPARISON OF MULTIPLICATIVE AND ADDITIVE HAZARD MODELS USING THE HAZARD AND SURVIVAL RATIO - Danardono, Danardono; Gunardi, Gunardi (MEDIA STATISTIKA, 2024)
The Cox multiplicative hazards regression and Aalen additive hazards regression models are widely used for survival data analysis. While the Cox model emphasizes hazard ratios or relative risks, the Aalen model focuses on relative survival or excess risks. This study compares the performance of these models through simulations of biomedical survival data. Results reveal no clear dominance of one model over the other, suggesting that both models should be employed to have a more thorough survival analysis.